TorakochirurgiaPresence of CD25 antigen on lymphocytes of patients treated for non-small cell lung cancer (NSCLC) - Rybojad, Paweł; Tabarkiewicz, Jacek; Koncewicz, Tomasz; Górniewski, Grzegorz; Roliński, Jacek; Goździuk, Kazimierz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Aim: The aim of the study was to evaluate the presence of CD25 antigen on lymphocytes in blood, tumour and lymph nodes of patients treated for NSCLC. Materials and methods: 29 people suffering from NSCLC were included in this study (Group 1). In addition we evaluated lymphocytes in blood of 15 healthy donors (Group 2). The percentages of lymphocyte subpopulations were compared between tissue compartments and between the two groups. The evaluation was done using monoclonal antibodies and flow cytometry. Results: We found the highest percentage of CD4 + /CD25 + in lymph nodes of NSCLC patients. The percentage of CD4 + /CD25 + was higher in tumour and in lymph nodes than in blood. Comparison of lymphocyte subpopulations between the two groups showed that in the blood of patients the percentages of CD4 + /CD25 + and CD19 + /CD25 + were higher and the percentage of CD8 + /CD25 + was lower than in Group 2. Conclusion: Lower percentage of CD8 + /CD25 + in the blood of patients treated for NSCLC might be explained with weakness of cellular immunodefence which could be connected with insufficient antitumour protection. Elevated levels of CD4 + /CD25 + and CD19 + /CD25 + in the blood of patients may be related to activation of the Th2 defence path. This could be the result of immunosuppressive tumour activity.